2020
DOI: 10.1007/s10068-020-00839-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microbiomes in three traditional starters and volatile components of the Chinese rice wines

Abstract: To understand the effect of microbial community on the flavor of fermented rice wine, microbiomes in three traditional starters (CMQ, NBQ, and YCQ) from different origins for making Chinese rice wines were evaluated and the volatile components of their rice wines were compared. The results showed that the dominant genera in CMQ were Pantoea, Bacillus, Rhizopus, and Candida, the dominant microorganisms in NBQ were Pediococcus, Lactobacillus, Acetobacter, Weissella, Bacillus, Rhizopus, Candida, and Aspergillus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…In this study, Pantoea was found to have a significant positive correlation with a few categories of VOCs during fermentation, such as higher alcohols (straight-chain fatty alcohols in YC and QTX, and branched-chain fatty alcohols in YQY), esters (acetic esters, methyl esters, isobutyl esters and isoamyl esters in YQY, and acetic esters in QTX), and fatty acids in QTX. This is in line with the previous reports [ 30 , 48 , 50 ], but there was no consistent pattern among different sub-regions ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, Pantoea was found to have a significant positive correlation with a few categories of VOCs during fermentation, such as higher alcohols (straight-chain fatty alcohols in YC and QTX, and branched-chain fatty alcohols in YQY), esters (acetic esters, methyl esters, isobutyl esters and isoamyl esters in YQY, and acetic esters in QTX), and fatty acids in QTX. This is in line with the previous reports [ 30 , 48 , 50 ], but there was no consistent pattern among different sub-regions ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 89%
“…Determination of volatile flavour compounds in samples by headspace HS‐SPME/GC‐MS, according to previously described methods with some modification (Liu et al., 2019; Yu et al., 2019; Chen et al., 2020). Briefly, the NaCl (1.5 g) and 20 μL of 2‐octanol (3.1 mg/L) were added to the 4.0 mL samples in 20 mL headspace vial.…”
Section: Methodsmentioning
confidence: 99%
“…have also reported Ralstonia in high abundance at the initial stage of persimmon wine fermentation; however, it gradually disappeared as the fermentation progressed and its role in winemaking is still unclear ( 28 ) . Pantoea is a conditionally pathogenic bacterium commonly found on plant surfaces ( 29 ) and frequently reported in koji ( 30 ) ; however, its role in winemaking is also unclear.…”
Section: Resultsmentioning
confidence: 99%